Histological assessment of the effect of neoadjuvant chemotherapy on conventional high grade osteosarcoma of the long bones - Thapa, JB (Journal of Pathology of Nepal, 2011)
A multidisciplinary team of an orthopaedic surgeon, medical oncologist, radiologist and pathologist was involved in the management of osteosarcoma cases. Four cases of osteosarcoma were examined for the effects of neoadjuvant chemotherapy. Total histological mapping was done to study the postchemotherapy biopsies. Two cases were good responders (more than 90% response), and two cases were poor responders (less than 90% response). Good responders had limb sparing surgery performed on them. Long term follow up results are awaited. Keywords: Neoadjuvant chemotherapy; Osteosarcoma; Total histological mapping; Tumour response DOI: 10.3126/jpn.v1i1.4455 Journal of Pathology of Nepal (2011) Vol.1, 60-62